Formation and Training of Peer Counselors on PKPR and Post-Covid-19 AKB Socialization - Sri Susilawati; Winda Windiyani; Dewi Nurdianti; Ade Kurniawati (AbdimasMu UMTAS, 2022)
Limited knowledge of students about adolescent reproductive health is a problem that is often found in Islamic boarding school. The behavior of teenagers who often wear clothes or towels alternating with friends will be very influential for the reproductive health of adolescents, and it is feared that it could become a medium of spread of covid-19. Therefore, it is necessary to establish youth counselors and training through the provision of information as well as counseling practices on Youth Care Health Services (PKPR) and Socialization of New Habit Adaptation (AKB) after covid-19 in Al-Ittihaad Islamic Boarding School Purbaratu. The purpose of this PKM activity is to train and provide information on the importance of maintaining health by paying attention to adolescent reproductive health behaviors in Islamic boarding school with the implementation of health protocols / adaptation of new habits (AKB), which in the end participants are able to relay the information that has been obtained during the training process to others. The method in this activity is the establishment of youth counselors from santri sons and daughters. Providing training by directly training participants conduct counseling practices to their peers in the post-covid-19 PKPR and AKB. Conduct health protocols to prevent the spread of covid-19 virus in Islamic boarding school. The result of this activity is the increasing knowledge and skills of peer counsellors about PKPR and AKB post-covid-19 in Islamic boarding school.Conclusion is that participants can know and better understand and apply directly the material about PKPR and AKB post-covid-19 in Islamic boarding school.